Knowledge on palliative care and associated factors among nurses working in Teaching Hospital Jaffna - Jerona, J.; Mathangi, J.; Jegapragash, V.; Nisahan, B. (University of Jaffna, 2024)
Palliative care is a multidisciplinary approach that improves the quality of life of patients and their families facing a life-threatening illness. It is entirely a new concept in developing countries. Identifying the level of knowledge on palliative care among nurses may result in the successful delivery of nursing care. The aim of the study is toassess the knowledge on palliative care and associated factors among the nurses working at Teaching Hospital, Jaffna. A hospital-based descriptive cross-sectional study was conducted among 276 nurses working in Teaching Hospital, Jaffna from June to August 2024 using stratified random sampling technique. A pre-tested self-administered questionnaire was used to collect the data. The knowledge level towards the palliative care was assessed using the modified Palliative care KnowledgeTest. It was converted to percentages and categorized as, inadequate (≤ 50%) and fair (>50%) according to the total score. Ethical clearance was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna. IBM SPSS 25 was used to analyze the data. Chi-squared test was used to find the association between knowledge and socio- demographic factors. Response rate of the study was 95.28%. Nearly three fourth of them (73%) were females, mean age was 33.47 years (SD=±7.391) and 71.1% had diploma in Nursing. Mean score of overall knowledge was 9.94 (SD=±2.512) with range from 3 to 15. Among them, 63.5% had fair and 36.5% had an inadequate knowledge level. Work experience (p=0.028) and heard about palliative care (p=0.003) showed statistically significant association with the knowledge of nurses towards palliative care. More than half of the respondents had fair knowledge. It is good to give more emphasis on palliative care while developing health policy, nursing curriculum, training on palliative care, and continuous professional development to enhance knowledge among nurses.
Keywords: Associated factors; Knowledge; Nurses; Palliative care